Proceedings of the 31st Annual ACM Symposium on User Interface Software and Technology 2018
DOI: 10.1145/3242587.3242659
|View full text |Cite
|
Sign up to set email alerts
|

Dynablock

Abstract: Figure 1. Dynablock is a rapid and reconstructable shape formation system, comprised of a large number of small physical elements. A) Dynablock's shape consists of 9 mm blocks which can be connected with omni-directional magnets. B-D) Dynablock leverages the 24 x 16 pin-based shape display as a parallel assembler of blocks, Dynablock is able to construct three-dimensional shapes in seconds. E) The example shows the output of a miniature model of table and a chair. The constructed shape is graspable and reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Year Published Main Contribution COCHRANE [3] 1862 development of multipoint moulding for sheet metal forming WALCZYK AND HARDT [4] 1998 examination of pin shape and matrix structure VALJAVEC [5] 1998 closed loop automatic adjustment control WALCZYK AND IM [6] 2000 implementation of closed-loop automatic adjustment control for hydraulic actuation WALCZYK AND LONGTIN [7] 2000 separated pins at larger distance and extension as a fixing device on CNC machine tables WALCZYK et al [8] 2003 densely packed pins with interpolation layer and a single vacuum chamber for CFRP parts OWODUNNI et al [9] 2004 fully computer-controlled adjustment by a commercial CNC system WANG AND YUAN [10] 2006 forming of very large aluminium sheet metal in several working steps mainly for large spherical objects TAN et al [11] 2007 forming of perforated titanium sheets for individually formed plates for skull reconstruction HAGEMANN [12] 2008 studies on multipoint moulding in injection moulding with the technical implementation WALCZYK AND MUNRO [13] 2009 second vacuum circuit under the interpolation layer for concave shapes KOC AND THANGASWAMY [14] 2011 adjustment and configuration for use in injection moulding BAYERISCHE FORSCHUNGSSTIFTUNG [15], SIMON et al [16], SIMON et al [17], ZITZLSBERGER [18], SIMON et al [19,20] 2011-2014 forming of plastic sheets with wide apart pins and a thick interpolation layer without vacuum for car prototype windows The further development of multipoint moulding with the main contribution of the authors is shown in Table 1 in a chronological order. densely packed pin field with silicon made interpolation layer and two vacuum circuits for CFRP parts, research of the influence of the thickness of the interpolation layer on dimpling SUZUKI et al [24,25] 2018 system for combination of small cuboids with magnets to larger objects as a faster alternative to additive manufacturing, the object creation is very similar to multipoint moulding An actual further development was made by WIMMER et al [23] relying on a densely packed pin field with vacuum support to enable forming of concave carbon fibre-reinforced plastic (CFRP) components (see Figure 3). Figure 3 shows that the concept used by WIMMER et al [23] follow the classical idea of multipoint ...…”
Section: Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Year Published Main Contribution COCHRANE [3] 1862 development of multipoint moulding for sheet metal forming WALCZYK AND HARDT [4] 1998 examination of pin shape and matrix structure VALJAVEC [5] 1998 closed loop automatic adjustment control WALCZYK AND IM [6] 2000 implementation of closed-loop automatic adjustment control for hydraulic actuation WALCZYK AND LONGTIN [7] 2000 separated pins at larger distance and extension as a fixing device on CNC machine tables WALCZYK et al [8] 2003 densely packed pins with interpolation layer and a single vacuum chamber for CFRP parts OWODUNNI et al [9] 2004 fully computer-controlled adjustment by a commercial CNC system WANG AND YUAN [10] 2006 forming of very large aluminium sheet metal in several working steps mainly for large spherical objects TAN et al [11] 2007 forming of perforated titanium sheets for individually formed plates for skull reconstruction HAGEMANN [12] 2008 studies on multipoint moulding in injection moulding with the technical implementation WALCZYK AND MUNRO [13] 2009 second vacuum circuit under the interpolation layer for concave shapes KOC AND THANGASWAMY [14] 2011 adjustment and configuration for use in injection moulding BAYERISCHE FORSCHUNGSSTIFTUNG [15], SIMON et al [16], SIMON et al [17], ZITZLSBERGER [18], SIMON et al [19,20] 2011-2014 forming of plastic sheets with wide apart pins and a thick interpolation layer without vacuum for car prototype windows The further development of multipoint moulding with the main contribution of the authors is shown in Table 1 in a chronological order. densely packed pin field with silicon made interpolation layer and two vacuum circuits for CFRP parts, research of the influence of the thickness of the interpolation layer on dimpling SUZUKI et al [24,25] 2018 system for combination of small cuboids with magnets to larger objects as a faster alternative to additive manufacturing, the object creation is very similar to multipoint moulding An actual further development was made by WIMMER et al [23] relying on a densely packed pin field with vacuum support to enable forming of concave carbon fibre-reinforced plastic (CFRP) components (see Figure 3). Figure 3 shows that the concept used by WIMMER et al [23] follow the classical idea of multipoint ...…”
Section: Authorsmentioning
confidence: 99%
“…Therefore, predicting the behaviour of the interpolation layer and the corresponding control of the system remains an issue to be dealt with [23]. densely packed pin field with silicon made interpolation layer and two vacuum circuits for CFRP parts, research of the influence of the thickness of the interpolation layer on dimpling SUZUKI et al [24,25] 2018 system for combination of small cuboids with magnets to larger objects as a faster alternative to additive manufacturing, the object creation is very similar to multipoint moulding An actual further development was made by WIMMER et al [23] relying on a densely packed pin field with vacuum support to enable forming of concave carbon fibrereinforced plastic (CFRP) components (see Figure 3). Figure 3 shows that the concept used by WIMMER et al [23] follow the classical idea of multipoint moulding by mounting rounded pinheads on studdings.…”
Section: Authorsmentioning
confidence: 99%
“…Despite differences in perceptual mechanisms, micro-and macro-roughness are hard for users to separate [67]. Prior work studied roughness with groove widths of 1mm up to 8mm [50], which is in the order of magnitude of the size of the gaps between the modules constituting future reconfigurable PUIs (e.g., [26,64,91,101]). On the kinesthetic level, surfaces with groove width of 5mm or 8mm give a kinesthetic feeling of detents -i.e.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, while non-self-actuated modules can reach small sizes (e.g., 2mm [34]), it is difficult for users to accurately manipulate very small modules. Previous work explored applications enabled by such modules, e.g., computer-assisted design on the physical prototype itself [91], animation directly with a physical prop [64,83], adapting the interface to the users' needs [82]. This modular approach promises to allow in the future for a large range of shape-change, while enabling high resolution and scalability [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation